Food quality standards in developing quality human capital: An Islamic perspective - Sazelin , Arif; Ridzwan, Ahmad (Academic Journal, 2011)
Islam outlines two important standards to ensure foods consumed by Muslims are good, quality, pleasant and healthy. The first is the most well-known, that is halal or lawful. The second, equally important, is tayyib or good quality. Some foods may be halal, but it may not be good (tayyib) for consumption. Therefore, food quality standards which based on the concept of halalan tayyiban (lawful and good) should be implemented to offer reassurance to those of the Muslim faith as well as developing good quality human capital. This paper, therefore, aims to (1) offer an instructive understanding of food quality standards in Islamic perspective and (2) discuss on the significance of the food quality standards which entail the holistic concept of halal and tayyib in developing good quality human capital. This concept paper is a qualitative in nature. The authors apply a document analysis approach through deep and intense readings of the previous texts and literature related to the topic. The authors thoroughly analyse the pertinent literature and develop the relationship between quality foods and quality human being. This paper reveals that consuming good quality food bounded by Islamic dietary laws has an intense relationship in generating good health which leads to developing good quality human capital.